Time above range for predicting the development of type 2 diabetes - Marco, Alejandra; Pazos-Couselo, Marcos; Moreno-Fernandez, Jesús; Díez-Fernández, Ana; Alonso-Sampedro, Manuela; Fernández-Merino, Carmen; Gonzalez-Quintela, Arturo; Gude, Francisco (Frontiers in Public Health, 2022)
Aim: To investigate the prognostic value of time range metrics, as measured by continuous glucose monitoring, with respect to the development of type 2 diabetes. Research Design and Methods: A total of 499 persons without diabetes from the general population were followed-up for 5 years. Time range metrics were measured at the start and medical records were checked over the period study. Results: Twenty-two subjects (8.3 per 1000 person-years) developed type 2 diabetes. After adjusting for age, gender, family history of diabetes, body mass index and glycated hemoglobin concentration, multivariate analysis revealed 'time above range' (TAR, i.e., with a plasma glucose concentration of >140 mg/dL) to be significantly associated with a greater risk (OR=1.06, CI 1.01-1.11) of developing diabetes (AUC=0.94, Brier=0.035). Conclusions: Time above range provides additional information to that offered by glycated hemoglobin to identify patients at a higher risk of developing type 2 diabetes in a population-based study.